(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Iskandar BS, Iskandar J. 2021. Kawung: Landraces, management, uses, and conservation based on moral versus economic interest among Outer Baduy community, South Banten, Indonesia. Biodiversitas 22: 5572-5584. The sugar palm or kawung (Arenga pinnata (Wurm) Merr.) has naturally or semi naturally grown in many rural areas of Banten and West Java. The sugar palm has social, economic, cultural, and ecological benefits for rural communities, but its population has dramatically decreased. This study aimed to access the knowledge, traditional management, uses and traditional conservation of sugar palm. This research used a qualitative method with an ethnoecological approach. The results showed that the Outer Baduy community has a rich knowledge of sugar palm. Two landraces of sugar palm are recognized by Outer Baduy mainly kawung gedé and kawung salompét. They have not intensively cultivated the sugar palm, but managed the kawung seedlings which grow naturally or assisted by civet or careuh in traditional agroforestry systems, including huma, reuma, leuweung lembur, and leuweung kolot. The weeds growing surrounding the seedlings are cleared, and then the seedlings will grow naturally and finally develop to mature trees. The sugar palm has been traditionally used for ecological, socio-economic, and cultural functions. The Outer Baduy community has traditionally conserved the sugar palm which grows in traditional agroforestry systems. The sugar palm trees, fruits, and the stems have never been cut, used as the sweetmeats, and made into sago flour, respectively, while the civets which have assisted distribution and regeneration of the sugar palm have never been hunted, and their habitat has never been destroyed.